Rekategorisasi Aset Kripto sebagai Objek Pajak Pertambahan Nilai Berdasarkan Asas Keadilan Perpajakan - Zulfahmi; Paramitha, Amelia Ayu; Rifan, Mohamad (RechtJiva, 2026)
This article examines the recategorization of crypto assets as objects of Value-Added Tax (VAT) through an analysis of Article 2 paragraph (1) of Minister of Finance Regulation Number 50 of 2025, which exempts crypto assets from VAT by equating them with securities. Two legal problems are addressed: whether the Minister of Finance possesses delegated authority to categorize crypto assets as securities, and how crypto assets should be recategorized so that their tax treatment fulfills the principle of fairness. Using normative legal research with statutory and conceptual approaches, the study finds that the Minister of Finance lacks valid delegated authority because none of the laws cited as the regulation's legal basis—the Financial Sector Development and Strengthening Law, the VAT Law, the Income Tax Law, and the General Tax Provisions Law expressly delegates such power, whereas the determination of tax objects is substantive material reserved for statute under Article 23A of the 1945 Constitution. Furthermore, applying the Howey Test and the 2026 SEC-CFTC Report, of six crypto asset categories analyzed only digital securities qualify as securities, while the remaining five should remain subject to VAT. Recategorization must therefore be implemented through hierarchical legal harmonization spanning the VAT Law, the P2SK Law, the regulation itself, and Financial Services Authority regulations.